The combined application of bleomycin with triamcinolone acetonide in port wine stains: inhibiting proliferation and recurrence of port wine stains - Quan-Feng Luo (SpringerOpen, 2023)
Abstract Background Port wine stains slowly grow thicker over time, nodules appear on the surface, and the color slowly deepens from pink to purple. Even after laser treatment, some port wine stains will recur and slowly grow, and the erythema appears again. The purpose of this study was to investigate the effectiveness of bleomycin in combination with triamcinolone acetonide in the treatment of inhibiting the proliferation and recurrence of port wine stains. Results Histopathological change: Before treatment, dense capillaries were distributed within the lesion, and blood fills the lumen. Lack of normal skin structure: After bleomycin and triamcinolone acetonide injection, the number of capillaries was significantly reduced, and fibrosis occurred in tissues. Changes in facial morphology: After treatment, the port wine stains became thinner, the asymmetry of the face was effectively improved, and the appearance have been significantly improved. After 5 years of follow-up, there were no recurrent cases. Conclusion Bleomycin and triamcinolone acetonide injection can effectively inhibit the proliferation of port wine stains and prevent port wine stains from recurring after treatment.